2009
DOI: 10.1007/s11664-009-0854-8
|View full text |Cite
|
Sign up to set email alerts
|

The Ni-rich Part of the Ni-P-Sn System: Isothermal Sections

Abstract: Due to the use of phosphorus-containing nickel substrates in microelectronics, understanding of their reaction with Sn-based solders and knowledge of the corresponding reaction products is highly important. Therefore the ternary Ni-P-Sn system was investigated experimentally using x-ray diffraction (XRD), scanning electron microscopy (SEM) + energy dispersive x-ray spectroscopy (EDX)/wavelength-dispersive x-ray spectroscopy (WDS), and differential thermal analysis (DTA). Sample preparation was done by alloying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…The liquid composition was deduced from the DTA measurements in consistency with other phase diagram information. [1] Information from the DTA was further enhanced by metallographic investigations of the solidification behavior of a number of samples, with the focus on the primary crystallization. These results are shown in Table IV, in which the primary crystallization is indicated by an asterisk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The liquid composition was deduced from the DTA measurements in consistency with other phase diagram information. [1] Information from the DTA was further enhanced by metallographic investigations of the solidification behavior of a number of samples, with the focus on the primary crystallization. These results are shown in Table IV, in which the primary crystallization is indicated by an asterisk.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in a study from our laboratory, three partial isothermal sections from the Ni-rich part of the Ni-P-Sn system were presented [1] based on X-ray diffraction (XRD) and electron probe microanalysis (EPMA). In the present investigation, the results of thermal analyses in the same region will be discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Ni-Sn-P phase diagram at 550°C, 16,17 formation of Ni 3 P will be avoided when the Sn concentration is greater than $10 wt.% ($5 at.%) and the P content is approximately 6-7 wt.%. Instead, the composition falls into the region of (Ni + Ni 3 Sn + Ni 21 P 6 Sn 2 ) at 550°C.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the composition falls into the region of (Ni + Ni 3 Sn + Ni 21 P 6 Sn 2 ) at 550°C. 16 Private communication with C. Schmetterer, the author of Refs. 16 and 17, revealed that the Ni-Sn-P phase diagram for temperatures below 550°C is not available because of practical difficulties.…”
Section: Introductionmentioning
confidence: 99%